House of hits the story of Houston's Gold Star/SugarHill Recording Studios - Bradley, Andy; Wood, Charles Roger (Brad and Michele Moore roots music series, 2010)
Founded in a working-class neighborhood in southeast Houston in 1941, Gold Star/SugarHill Recording Studios is a major independent studio that has produced a multitude of influential hit records in an astonishingly diverse range of genres. Its roster of recorded musicians includes Lightnin' Hopkins, George Jones, Willie Nelson, Bobby "Blue" Bland, Junior Parker, Clifton Chenier, Sir Douglas Quintet, 13th Floor Elevators, Freddy Fender, Kinky Friedman, Ray Benson, Guy Clark, Lucinda Williams, Beyoncé and Destiny's Child, and many, many more. In House of Hits, Andy Bradley and Roger Wood chronicle the fascinating history of Gold Star/SugarHill, telling a story that effectively covers the postwar popular music industry. They describe how Houston's lack of zoning ordinances allowed founder Bill Quinn's house studio to grow into a large studio complex, just as SugarHill's willingness to transcend musical boundaries transformed it into of one of the most storied recording enterprises in America. The authors offer behind-the-scenes accounts of numerous hit recordings, spiced with anecdotes from studio insiders and musicians who recorded at SugarHill. Bradley and Wood also place significant emphasis on the role of technology in shaping the music and the evolution of the music business. They include in-depth biographies of regional stars and analysis of the various styles of music they represent, as well as a list of all of Gold Star/SugarHill's recordings that made the Billboard charts and extensive selected historical discographies of the studio's recordings.
Keywords: SugarHill Recording Studios; Gold Star Studios; Sound recording industry : Texas : Houston : History